A typical C-type lectin, perlucin-like protein, is involved in the innate immune defense of whiteleg shrimp Litopenaeus vannamei. Issue 103 (August 2020) - Bi, Jingxiu; Ning, Mingxiao; Xie, Xiaojun; Fan, Weifeng; Huang, Yanlan; Gu, Wei; Wang, Wen; Wang, Li; Meng, Qingguo
Abstract: C-type lectins are a large group of the pattern-recognition proteins, and have been reported to be involved in invertebrate innate immunity, such as cell adhesion, bacterial clearance, phagocytosis, prophenoloxidase activation and encapsulation. Here, a perlucin-like protein (PLP), a typical C-type lectin, was identified from the cDNA library of the shrimp, Litopenaeus vannamei . LvPLP contains a 540 bp open reading frame, encoding a protein of 179 amino acids that includes a single carbohydrate-recognition domain. Phylogenetic analysis showed that LvPLP was clustered into a single group together with other perlucins from molluscs. Quantitative real-time PCR revealed that LvPLP was expressed mainly in the hemocytes, hemolymph, heart and gills. The transcription of LvPLP was significantly induced at 9 h by both Gram − bacteria Vibrio parahaemolyticus and Vibrio anguillarum . Meanwhile, recombinant LvPLP (rLvPLP) bound directly to lipopolysaccharide and peptidoglycan with different affinity. rLvPLP showed a strong ability to bind to Gram + ( Staphylococcus aureus and Bacillus subtilis ) and Gram − bacteria ( V . parahaemolyticus and V . anguillarum ), and could induce agglutination of V . parahaemolyticus and V . anguillarum, but not S . aureus and B . subtilis in the presence Ca 2+ . Further study showed that when LvPLP was knocked down by RNAi, three phagocytosis-related genes ( peroxinectin, mas-like protein and dynamin ) and four antimicrobial peptide (AMP) genes ( crustin, ALF1, ALF2 and ALF3 ) were significantly decreased. Altogether, these results demonstrated that LvPLP played a vital role in L . vannamei immune response towards bacterial challenge by binding and agglutinating bacteria and influencing phagocytosis and AMP expression. Highlights: A C-type lectin ortholog was obtained from L . vannamei and named LvPLP. LvPLP is involved in immune response to pathogen infection. LvPLP directly agglutinate bacterial pathogens to restrict their spread in the plasma. LvPLP is involved in regulating the innate immunity of L. vannamei by regulating phagocytosis and AMP expression.